Practical mobile forensics : forensically investigate and analyze iOS, Android, and Windows 10 Devices /: forensically investigate and analyze iOS, Android, and Windows 10 Devices. (2020) - Tamma, Rohit; Skulkin, Oleg; Mahalik, Heather; Bommisetty, Satish
No abstract available